2021
DOI: 10.1002/alz.050965
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacterium breve decreases Aβ production via the upregulation of ADAM10 level and attenuates microglia activation in an APP knock‐in mouse model of Alzheimer’s disease

Abstract: Background: Probiotics supplementation reinstates microbiome diversity and improves brain function, including memory and learning abilities, although the molecular mechanisms have not been fully elucidated. In the current study, we investigated the effects of orally supplemented Bifidobacterium breve MCC1274 (B. breve MCC1274, synonym B. breve A1) on memory impairment and Alzheimer's disease (AD) pathogenesis in amyloid precursor protein knock-in (APP-KI) mice, (App NL-G-F ).Method: Three-month-old App NL-G-F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Their intake could positively affect brain activity by the synthesis of neurotransmitters, expression of receptors producing neuromodulators and neurotransmitters, anti-inflammatory, and antioxidant effects, or the impact on the endocrine system. Studies in animal models of AD have shown that probiotics can alleviate memory and cognitive deficits [ 103 , 104 , 105 , 106 ]. The number of publications on the influence of probiotic supplementation on mental health improvement in people with Alzheimer’s disease is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Their intake could positively affect brain activity by the synthesis of neurotransmitters, expression of receptors producing neuromodulators and neurotransmitters, anti-inflammatory, and antioxidant effects, or the impact on the endocrine system. Studies in animal models of AD have shown that probiotics can alleviate memory and cognitive deficits [ 103 , 104 , 105 , 106 ]. The number of publications on the influence of probiotic supplementation on mental health improvement in people with Alzheimer’s disease is limited.…”
Section: Resultsmentioning
confidence: 99%
“…It was also discovered that Bifidobacterium can alleviate CI by improving synaptic function and increasing BDNF expression. For example, Jung et al 119 found that Bifidobacterium breve MCC1274 rescues cognitive deficits in App NL–G–F mice by attenuating microglial activation, downregulating neuroinflammatory cytokines and increasing postsynaptic protein levels in the hippocampus. In contrast, Bifidobacterium longum BORI and Bifidobacterium bifidum BGN4 improve synaptic plasticity and restore learning and memory by ameliorating neuroinflammatory responses and inhibiting amyloidosis and apoptosis.…”
Section: Interventionsmentioning
confidence: 99%